Extreme hyperferritinemia: etiological spectrum and impact on prognosis - N. Belfeki; A. Strazzulla; M. Picque; S. Diamantis (PAGEPress Publications, 2020)
Hyperferritinemia can be the result of inflammation, infection, iron overload, or other uncommon pathologies including hemophagocytic lymphohistiocytosis (HLH). The significance of its elevation and its association with poor prognosis and critical clinical situations is unclear. To study the spectrum of diagnosis associated with elevated serum ferritin, we made a retrospective review of patients admitted to our center from 2015 and 2017 with serum ferritin levels above 2000 μg L-1. The H score was retrospectively assessed in all cases to evaluate the possible presence of HLH. The degree of ferritinemia found was compared with the evaluation of the undelying diagnosis and the results of laboratory examinations. A total of 77 patients were identified with a serum ferritin level >2000 μg L-1. Hematological malignancy was the most prevalent diagnosis with n=20; severe infection was next with n=14. Eleven patients were diagnosed with HLH. The hemophagocytosis pictures on bone marrow smear and mortality rate were significantly correlated with ferritin level above 6000 μg L-1 (p<0.01). The comparison of the HLH subgroup with the rest of the cohort showed that fever, cytopenia (anemia, leucopenia, neutropenia and thrombocytopenia), hemophagocytosis pictures, and major liver disturbances were significantly increased in the HLH subgroup. The H score was significantly elevated in the subgroup of patients with ferritin above 6000 μg L-1, with a significatively higher probability of HLH (p<0.01). The mortality rate at 3 months was significantly increased in the HLH subgroup. Extreme hyperferritin cannot be considered as a specific marker for the diagnosis. The cut off of 6000 μg L-1 is significantly associated with HLH diagnosis. The H score is an interesting screening tool that physicians should use to rule out the probability of HLH when facing critical clinical situations.